2011
DOI: 10.1128/mcb.05383-11
|View full text |Cite
|
Sign up to set email alerts
|

c-Abl-Mediated Tyrosine Phosphorylation of the T-bet DNA-Binding Domain Regulates CD4+ T-Cell Differentiation and Allergic Lung Inflammation

Abstract: The tyrosine kinase c-Abl is required for full activation of T cells, while its role in T-cell differentiation has not been characterized. We report that c-Abl deficiency skews CD4 ؉ T cells to type 2 helper T cell (Th2) differentiation, and c-Abl ؊/؊ mice are more susceptible to allergic lung inflammation. c-Abl interacts with and phosphorylates T-bet, a Th1 lineage transcription factor. c-Abl-mediated phosphorylation enhances the transcriptional activation of T-bet. Interestingly, three tyrosine residues wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
(55 reference statements)
0
18
0
Order By: Relevance
“…Published data (13, 14, 16) suggested that within T-bet, S52, Y76 and S224 phosphorylation sites could be important for T-bet’s ability to induce IFNγ expression by influencing either its ability to bind DNA and/or interact with chromatin remodeling complexes. A distinct phosphorylation site, S508, has been previously demonstrated to be important for suppression of IL-2 production by T-bet (15).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Published data (13, 14, 16) suggested that within T-bet, S52, Y76 and S224 phosphorylation sites could be important for T-bet’s ability to induce IFNγ expression by influencing either its ability to bind DNA and/or interact with chromatin remodeling complexes. A distinct phosphorylation site, S508, has been previously demonstrated to be important for suppression of IL-2 production by T-bet (15).…”
Section: Resultsmentioning
confidence: 99%
“…Previously 3 other T-bet phosphorylation sites within the T-box region (Y219/Y265/Y304) have been demonstrated to be crucial for T-bet’s ability to bind DNA proximal to its target genes (16). T-bet promotes the expression of its target genes via two mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luciferase Assay-Experiments were performed as described (20). Briefly, HEK293 cells in 12-well plates were transfected with pRL-TK (Promega, Madison, WI), and each of Sirt1-luc plasmids, along with EGR2, EGR3, or FoxO3a expression plasmids or both as indicated.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, Runx3 is able to interact with Gata3 (Yagi et al 2010), as does phosphorylated Tbet, and this interaction inhibits Th2 differentiation by blocking the binding of Gata3 to target genes (Hwang et al 2005b). Increased levels of phosphorylated Tbet correlated with increased IFNγ expression while inhibition of Tbet phosphorylation resulted in increased Th2 differentiation (Chen et al 2011a). Tbet also binds directly to the Gata3 gene and increases restrictive histone modifications to repress Gata3 expression (Zhu et al 2012).…”
Section: Master Regulators Of Cd4 T Cell Differentiationmentioning
confidence: 99%